Successful management of cardiac electrical storm after aortic valve replacement using stellate ganglion block: a case report - Xinyi Zhang; Yi Guo; Shuo Chang (Journal of Cardiothoracic Surgery)
Abstract Cardiac electrical storm (CES) is a life-threatening state of electrical instability characterized by 3 or more episodes of sustained ventricular arrhythmia within 24 h. The application of stellate ganglion block for the treatment of cardiac surgery has rarely been reported. Herein, we report a patient whose ventricular arrhythmia was completely relieved after receiving a stellate ganglion block. We present a case of a 35-year-old male who underwent aortic valve replacement. The patient who had aortic valve stenosis was scheduled for aortic valve replacement and simultaneous tricuspid valvuloplasty. After sedation was discontinued, malignant arrhythmias recurred. We performed stellate ganglion block for patient. As aresult, the patient achieved a complete resolution of symptoms and successfully resumed a normal productive life one year post-surgery. Stellate ganglion block is a safe and effective treatment for patients with ventricular tachycardia unresponsive to drug therapy following cardiac surgery.